Wykwintna kuchnia na kazda okazje : ponad 600 kolorowych zdjec--ilustruje--350 przepisow. (Warszawa : Muza SA, 1997)
A translation of "Kochen leichtgemacht", a bookof recipes of elegant cuisine for every occasion.
At head of title: Burda.
Includes index.
Keywords: Cooking